Exploring and describing the facilitators and barriers during shift handover between critical care nurses in a private hospital in Gauteng - Coetzee-Prinsloo, Isabel M. (University of Pretoria, 2025)
Dissertation (MNurs (Nursing Science))--University of Pretoria, 2024.